R Corps: When Should Corporate Values Receive Religious Protection - Scott,Inara; Brown,Elizabeth; Yordy,Eric (Berkeley Business Law Journal, 2020)
In this article, we explain how a corporation might invoke religious freedom claims in order to protect corporate values such as diversity, equality, sanctuary, or women’s access to reproductive care which are not exclusively associated with a religion, and are often held by secular entities. In order to do so, we must address the following unresolved legal issues: 1) How can one define whether a set of beliefs are “religious” when those beliefs are held not just by a single individual, but by a diverse collection of individuals? 2) Does the meaning of religion change when it is no longer exercised by a human being but instead by a corporation? 3) Importantly, how would a court evaluate the religious claims of a business entity made up of diverse owners, members, and/or shareholders? And 4) What are the broader consequences, benefits and detriments of protecting such claims?
Keywords: Business Law